2017
DOI: 10.1589/jpts.29.198
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, knowledge and behavior of Japanese physical therapists with regard to evidence-based practice and clinical practice guidelines: a cross-sectional mail survey

Abstract: [Purpose] This study aimed to investigate Japanese physical therapists’ attitudes of evidence-based practice and clinical practice guidelines. [Subjects and Methods] In 2014, a cross-sectional postal mail survey using a self-administered questionnaire was conducted. Of 2,982 physical therapists belonging to the Chiba Prefecture Physical Therapist Association, 1,000 were randomly selected. The questionnaire comprised 42 items pertaining to the attitudes of and behavior toward evidence-based practice and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 19 publications
(37 reference statements)
2
41
0
1
Order By: Relevance
“…Contrastingly, it is reported that the consciousness of Japanese therapists on CPGs and the evidence are low compared to foreign countries. Fujimoto et al [27] researched the consciousness of EBP while targeting Japanese physiotherapists. Although 54.9% perceived the signi cance of CPGs, the usage was below 30% [27], which is way below the 61% usage in foreign countries [28].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Contrastingly, it is reported that the consciousness of Japanese therapists on CPGs and the evidence are low compared to foreign countries. Fujimoto et al [27] researched the consciousness of EBP while targeting Japanese physiotherapists. Although 54.9% perceived the signi cance of CPGs, the usage was below 30% [27], which is way below the 61% usage in foreign countries [28].…”
Section: Resultsmentioning
confidence: 99%
“…One reason for this could be the lack of therapist education on the usage of CPGs in Japan [27]. In particular, perspectives on applicable situations lack in practical education in Japan [34].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations